Ultrafast laser ablation, intrinsic threshold, and nanopatterning of monolayer molybdenum disulfide - Joel M. Solomon; Sabeeh Irfan Ahmad; Arpit Dave; Li-Syuan Lu; Fatemeh HadavandMirzaee; Shih-Chu Lin; Sih-Hua Chen; Chih-Wei Luo; Wen-Hao Chang; Tsing-Hua Her (Scientific Reports, 2022)
Abstract Laser direct writing is an attractive method for patterning 2D materials without contamination. Literature shows that the ultrafast ablation threshold of graphene across substrates varies by an order of magnitude. Some attribute it to the thermal coupling to the substrates, but it remains by and large an open question. For the first time the effect of substrates on the femtosecond ablation of 2D materials is studied using MoS2 as an example. We show unambiguously that femtosecond ablation of MoS2 is an adiabatic process with negligible heat transfer to the substrates. The observed threshold variation is due to the etalon effect which was not identified before for the laser ablation of 2D materials. Subsequently, an intrinsic ablation threshold is proposed as a true threshold parameter for 2D materials. Additionally, we demonstrate for the first time femtosecond laser patterning of monolayer MoS2 with sub-micron resolution and mm/s speed. Moreover, engineered substrates are shown to enhance the ablation efficiency, enabling patterning with low-power ultrafast oscillators. Finally, a zero-thickness approximation is introduced to predict the field enhancement with simple analytical expressions. Our work clarifies the role of substrates on ablation and firmly establishes ultrafast laser ablation as a viable route to pattern 2D materials.